Cardiopulmonary bypass in a child with erythropoietic protoporphyria. (24th November 2021) - Pathman, Lydia; Bennett, Martin; d'Udekem, Yves; Phillips, Roderic
Abstract: Children with erythropoietic porphyria are generally under the care of paediatric dermatologists. When these children undergo major surgery, they are at risk of unusual complications due to their photosensitivity. Dermatologists may be consulted prior to surgery for advice. We describe a case of a child with erythropoietic porphyria undergoing open heart surgery, utilising an exchange transfusion alongside other strategies to minimise the risk of photosensitivity‐induced haemolysis.